Pengaruh NurseTheraCom Berbasis Microlearning terhadap Keterampilan Komunikasi Terapeutik Mahasiswa Keperawatan - Hendra Priyatnanto; Yunita Dwi Anggreini (Khatulistiwa Nursing Journal, 2026)
Background: Therapeutic communication is a mandatory skill for nurses. This study examines the microlearning method "NurseTheraCom," a web platform containing materials, quizzes, and videos designed to improve the competency of nursing students. Objective: This study aims to examine the effect of the NurseTheraCom micro-learning method on improving students' knowledge and therapeutic communication skills. Method: This research is a quasi-experimental study with a pretest and posttest nonequivalent control group design. The respondents in this study were nursing students from STIKes YARSI Pontianak, selected using purposive sampling technique. The inclusion criteria for respondents are active nursing students at STIKes YARSI Pontianak who have already taken the nursing communication course. A total of 60 nursing students participated in a microlearning intervention, with skills assessed thru questionnaires before and after the intervention and analyzed using a paired t-test. Results: There was a significant increase in knowledge (high category from 23.3% to 81.67%) and skills (high category from 15.0% to 78.33%). The average skill score increased from 20.00 to 32.67 (p=0.002). Conclusion: The NurseTheraCom microlearning method is effective in improving nursing students' knowledge and therapeutic communication skills, potentially serving as a tool for continuous training to enhance service quality.